Impacts of patient and family engagement in hospital planning and improvement: qualitative interviews with patient/family advisors and hospital staff - Natalie N Anderson; Kelly Dong; G. Ross Baker; Lesley Moody; Kerseri Scane; Robin Urquhart; Walter P Wodchis; Anna R Gagliardi (BMC, 2022)
Abstract Background Patient engagement (PE) in hospital planning and improvement is widespread, yet we lack evidence of its impact. We aimed to identify benefits and harms that could be used to assess the impact of hospital PE. Methods We interviewed hospital-affiliated persons involved in PE activities using a qualitative descriptive approach and inductive content analysis to derive themes. We interpreted themes by mapping to an existing framework of healthcare performance measures and reported themes with exemplar quotes. Results Participants included 38 patient/family advisors, PE managers and clinicians from 9 hospitals (2 < 100 beds, 4 100 + beds, 3 teaching). Benefits of PE activities included 9 impacts on the capacity of hospitals. PE activities involved patient/family advisors and clinicians/staff in developing and spreading new PE processes across hospital units or departments, and those involved became more adept and engaged. PE had beneficial effects on hospital structures/resources, clinician staff functions and processes, patient experience and patient outcomes. A total of 14 beneficial impacts of PE were identified across these domains. Few unintended or harmful impacts were identified: overextended patient/family advisors, patient/family advisor turnover and clinician frustration if PE slowed the pace of planning and improvement. Conclusions The 23 self reported impacts were captured in a Framework of Impacts of Patient/Family Engagement on Hospital Planning and Improvement, which can be used by decision-makers to assess and allocate resources to hospital PE, and as the basis for ongoing research on the impacts of hospital PE and how to measure it.